The Effect of Alendronate and Intranasal Calcitonin Treatments on Bone Mineral Density in Men with Idiopathic Osteoporosis - F. Taşçıoğlu; Ayşe Aydemir; C. Öner (Galenos Yayinevi, 2003)
The aim of this study was to compare the effect of alendronate and calcitonin treatments on bone mineral density (BMD) in men with idiopathic osteoporosis. After performing a detailed clinical and laboratory assessment in order to eliminate secondary factors that can lead to osteoporosis, fifty-two men with idiopathic osteoporosis were randomly assigned to two groups: 28 patients in the first group received intranasal salmon calcitonin at a dosage of 200 IU/ day and they also received daily doses of 1000 mg calcium supplements. Twenty-four patients in the second group used 10 mg alendronate/day and 1000 mg calcium/day. DXA was used for the measurement of BMD of the lumbar spine and proximal femur before and after the study period. At the end of the treatment, alendronate produced significant increases in BMD at the lumbar spine (p< 0.001), femur neck (p<0.05), trochanteric region (p<0.05) and at the Ward triangle (p<0.05). In contrast, only a significant increase in BMD of the lumbar spine was observed with calcitonin treatment (p< 0.001) and intranasal calcitonin treatment failed to increase BMD in the femur neck, trochanteric region and Ward triangle (p>0.05). When the groups were compared with each other, a significant increase in lumbar BMD was obtained in favor of alendronate treatment (p<0.05). In conclusion, alendronate seemed to be more effective than calcitonin, increasing both spinal and femoral BMD, for the treatment of idiopathic male osteoporosis.